2017
DOI: 10.1108/pm-08-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing real estate students’ academic performance in an emerging economy

Abstract: Purpose The purpose of this paper is to examine the extent to which variations in gender, socioeconomic and academic background influence real estate students’ academic performance in Nigeria. Design/methodology/approach Data for the study were collected using self-administered questionnaire, served on final year real estate students in two of the three Federal universities offering real estate as a course in Southwestern Nigeria. Data collected were analyzed using mean, frequency count, percentages, indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
10
2
1
Order By: Relevance
“…Sci. Review 9 (1) 41 -49 (2021) from Ayodele, Oladokun and Oladokun (2017). Response options were presented in 5-point Likert-scales anchored by 1=strongly disagree and 5=strongly agree to express the degree of agreement or disagreement.…”
Section: Methodsmentioning
confidence: 99%
“…Sci. Review 9 (1) 41 -49 (2021) from Ayodele, Oladokun and Oladokun (2017). Response options were presented in 5-point Likert-scales anchored by 1=strongly disagree and 5=strongly agree to express the degree of agreement or disagreement.…”
Section: Methodsmentioning
confidence: 99%
“…Tsirkas et al (2020) submitted that neglect of soft skill development across institutions, the inadequacy of training and development of soft skills in the working environments and underestimation of soft skills' value by the employees and reluctance in developing them influenced skill gap among graduate employees. The prevalence of students studying courses that they never intended due to the inability of students to get their desired course also contributes to the rising skill gap, especially in the real estate sector (Ayodele et al , 2017). This could lead to reluctance in acquiring and developing the needed skill sets expected of real estate professionals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the study concluded that the negative perception that real estate discipline required less academic rigor was the principal reason for the poor academic performance of male students. In a follow-up study to the earlier work of Ayodele et al (2016), the article by Ayodele et al (2017) examined the effects of gender variation, socioeconomic and academic background as factors influencing real estate students’ academic performance in Nigeria. The sample comprised 152 final year real estate students from two federal universities in the southwestern part of Nigeria.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…In Nigeria, notable contributions to this existing body of the literature are recent and location specific. Most of these studies have investigated the academic performance of real estate students through the effects of socioeconomic, gender variation and academic background (Ayodele et al , 2016, 2017; Olatunji et al , 2016; Peter et al , 2016). Others have examined the academic progress of real estate students in the individual subject using grade earned in other co-requisite subjects (Ataguba et al , 2017).…”
Section: Introductionmentioning
confidence: 99%